Three-dimensional molded object and method for manufacturing the same

By using a high-melting point polymer powder composition with controlled temperature and specific additives, the method addresses warpage and thermal deterioration in 3D printing, resulting in high-quality, heat-resistant 3D structures.

JP2024177118APending Publication Date: 2024-12-19TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024091886
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-02-27
Filing Date
2024-06-06
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing 3D printing methods using high-melting point polymers face issues with warpage and thermal deterioration of the polymer powder composition and the 3D printing apparatus, leading to poor dimensional accuracy and oxidative coloring of the objects.

Method used

A method for producing 3D structures using a polymer powder composition with a melting point of 200°C or higher, controlled at a powder bed temperature of 200°C or lower, incorporating polyamide with specific particle sizes and reinforcing materials to minimize warpage and thermal deterioration.

Benefits of technology

The method achieves 3D structures with minimal warpage and excellent heat resistance, suppressing thermal deterioration and oxidative coloring, while maintaining the integrity of the 3D printing apparatus and the quality of the printed objects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177118000003
    Figure 2024177118000003
  • Figure 2024177118000001
    Figure 2024177118000001
  • Figure 2024177118000002
    Figure 2024177118000002
Patent Text Reader

Abstract

To provide a method for manufacturing a three-dimensional molded object, which can obtain a three-dimensional molded object having a small warpage and an excellent heat resistance while suppressing thermal deterioration to a polymer powder composition and heat load to a three-dimensional molding device.SOLUTION: There is provided a three-dimensional molded object that is obtained by a powder bed fusion bonding method, and which is obtained by using a polymer powder composition that is configured in that: when a test piece with 10 mm wide, 80 mm long and 4 mm thickness is prepared so that the 80 mm length is perpendicular to a direction in which a re-coater is moved, and the 4 mm thickness is a height direction in which a material powder is laminated, a warpage in the length direction of the test piece with a 80 mm length is 1.5 mm / 10 cm or less and a melting point of the polymer that composes the three-dimensional molded object is 200°C or higher, and a yellowness of the three-dimensional molded object is 10 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a three-dimensional object and a method for producing the three-dimensional object. [Background technology]

[0002] Known techniques for manufacturing three-dimensional objects (hereinafter sometimes referred to as "modeled objects") include material extrusion, powder bed fusion, liquid vat photopolymerization, and sheet lamination. Among these, in the powder bed fusion method, a layer of powder is provided, and then selectively melted at a position corresponding to the cross section of the object, and these layers are bonded and laminated to form a three-dimensional object. Here, methods for selectively melting powder include selective laser sintering using a laser, selective absorption sintering using a melting assistant, and selective suppression sintering in which the areas not to be melted are masked. Compared to other modeling methods, the powder bed fusion method has the advantage that it is suitable for precision modeling and does not require support members during modeling.

[0003] Taking advantage of their excellent mechanical properties and dimensional accuracy, the three-dimensional objects obtained by the above-mentioned method are being considered for use in a variety of fields, such as mobility applications in automobiles, aviation, and space, medical applications in prosthetic limbs, braces, hearing aids, and catheters, sports applications, and electrical and electronic materials. Traditionally, three-dimensional objects were used for prototyping to confirm shapes, but in recent years, application development has progressed, and they are being considered for functional prototyping to confirm the performance of designed shapes and for final product applications in which three-dimensional objects are actually used, and there is an increasing demand for heat resistance and mechanical properties.

[0004] For this reason, research has been conducted into three-dimensional objects made from polymer powders with high melting points. In powder bed fusion, the powder is selectively melted and then cooled to produce an object, but high-melting-point polymers have high crystallinity, and so undergo large volumetric shrinkage during crystallization on cooling, resulting in issues such as rounded corners and warping of the edges of the three-dimensional object.

[0005] To address these issues, Patent Document 1 discloses a technique for suppressing warping of a three-dimensional object by increasing the crystallinity of the polymer powder through annealing, thereby enabling the powder bed temperature to be raised to near the melting point. Patent Document 2 discloses a technique for obtaining a three-dimensional object without warping by using a polyamide powder with a sharp melting behavior, which does not melt even if there is a distribution in the powder bed temperature. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-196983 A [Patent Document 2] International Publication No. 2022-181633 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in Patent Document 1, particles of PBT with a melting point of 218°C or PA66 with a melting point of 265°C are used to perform 3D modeling at a part bed temperature of the melting point ±3°C, which raises concerns about thermal degradation of the polymer powder composition, which may lead to difficulty in recovering and using the powder, and deterioration of the physical properties of the modeled object. In Patent Document 2, particles with a melting point of 217°C are used to perform 3D modeling with the part bed temperature initially set to -15°C below the melting point. In this case, it was found that there are still problems with thermal degradation of the polymer powder composition and the thermal load on the 3D modeling device not being sufficiently suppressed.

[0008] Therefore, an object of the present invention is to provide a method for producing a three-dimensional object that can obtain a three-dimensional object with little warping and excellent heat resistance while suppressing thermal degradation of a polymer powder composition and thermal load on a three-dimensional modeling device, in particular, to provide a three-dimensional object that has a high melting point and is suppressed from being discolored by heat. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention has the following configuration. <1> A test piece 10 mm wide, 80 mm long and 4 mm thick is prepared with the 80 mm length direction perpendicular to the direction of recoater movement and the 4 mm thickness direction corresponding to the height direction in which the material powder is layered. The warp of the test piece in the 80 mm length direction is 1.5 mm / 10 cm or less. This is a three-dimensional object obtained by a powder bed fusion method using a polymer powder composition, wherein the melting point of the polymer constituting the three-dimensional object is 200°C or higher and the yellowness of the three-dimensional object is 10 or less. <2> The polymer constituting the three-dimensional object is polyamide. <1> The three-dimensional object according to claim 1. <3> The polyamide includes at least one polyamide selected from polyamide 6, polyamide 610, polyamide 66, and a copolymer including any of these. <1> , <2> The three-dimensional object according to claim 1. <4> The three-dimensional object contains 10% by mass or more and 80% by mass or less of a reinforcing material. <1> ~ <3> The three-dimensional object according to claim 1. <5> A three-dimensional object obtained by powder bed fusion using a polymer powder composition, in which a test piece having a width of 10 mm, a length of 80 mm, and a thickness of 4 mm is prepared so that the 80 mm length direction is parallel to the direction in which the recoater moves, and the 4 mm thickness direction is the height direction in which the material powder is layered. The test piece has a heat distortion temperature of 160°C or higher when measured under a load of 0.45 MPa according to JIS K7191-1 (2015). <1> ~ <4> The three-dimensional object according to claim 1. <6> The three-dimensional object includes a surface having a surface roughness of less than 20 μm. <1> ~ <5> The three-dimensional object according to claim 1. <7> A method for manufacturing a three-dimensional object by powder bed fusion bonding using a polymer powder composition, in which a test piece 10 mm wide, 80 mm long, and 4 mm thick is prepared with the 80 mm length direction perpendicular to the direction in which the recoater moves and the 4 mm thickness direction corresponding to the height direction in which the material powder is layered, and the warp of the test piece in the 80 mm length direction is 1.5 mm / 10 cm or less, wherein the melting point of the polymer constituting the polymer powder composition is 200°C or higher and the temperature of the uppermost powder layer in the powder bed is 200°C or lower. <8> Regarding the lightness L(1) of the polymer powder composition before three-dimensional modeling and the lightness L(2) of the polymer powder composition remaining around the modeled object after three-dimensional modeling, L(2) / L(1) is 0.85 or more and 1.05 or less; <7> A method for producing a three-dimensional object according to claim 1. <9> The polymer powder composition comprises a polyamide powder having a D50 particle size of 1 μm or more and 100 μm or less. <7> , <8> A method for producing a three-dimensional object according to claim 1. <10> The polymer powder composition contains 10% by mass or more and 80% by mass or less of a reinforcing material having an average major axis of 3 μm or more and 120 μm or less and an average major axis / average minor axis ratio of 2 or more and 12 or less. <7> ~ <9> A method for producing a three-dimensional object according to claim 1. <11> The apparent density / tap density of the reinforcing material is 0.50 or more and 1.00 or less. <10> A method for producing a three-dimensional object according to claim 1. <12> The shrinkage rate of the 3D object on the XY plane relative to the CAD data for 3D printing is 2% or less. <7> ~ <11> A method for producing a three-dimensional object according to claim 1. <13> The temperature of the polymer powder composition fed to the powder bed is 140° C. or higher; <7> ~ <12> A method for producing a three-dimensional object according to claim 1. <14> The pre-stacking height is 15 mm or more. <7> ~ <13> A method for producing a three-dimensional object according to claim 1. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a three-dimensional object with excellent heat resistance and small warpage while suppressing thermal deterioration of the polymer powder composition and thermal load on the three-dimensional modeling device. Furthermore, it is possible to obtain a three-dimensional object with a high melting point and suppressed oxidative coloring. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a manufacturing apparatus for a three-dimensional object according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The method for producing a three-dimensional object according to the present invention will be described in detail below.

[0013] In the past, in order to obtain a three-dimensional object with excellent heat resistance, the three-dimensional modeling device also needed to have excellent heat resistance, and there was a problem that parts of the device deteriorated when three-dimensional modeling was performed at a high temperature. In addition, when a high-melting point polymer powder composition for obtaining a three-dimensional object with excellent heat resistance is three-dimensionally modeled at a high temperature, there was a problem that it was subject to thermal deterioration such as oxidative coloring, powder aggregation, and decomposition of additives. However, in the past, the biggest challenge in three-dimensional modeling was the dimensional accuracy of the obtained three-dimensional object and suppression of warping, and in order to meet this challenge, a technology for increasing the modeling temperature as much as possible was important. The present invention relates to a technology for obtaining a three-dimensional object with excellent heat resistance and small warping while suppressing thermal deterioration of the polymer powder composition and the thermal load on the three-dimensional modeling device by lowering the modeling temperature as much as possible, which is the opposite of the past.

[0014] In other words, the method for producing a three-dimensional object of the present invention is a method for producing a three-dimensional object by a powder bed fusion method using a polymer powder composition with a high melting point, and is characterized in that the melting point of the polymer constituting the polymer powder composition is 200°C or higher, and the three-dimensional object is produced at a temperature of the uppermost powder layer of the powder bed of 200°C or lower.

[0015] The three-dimensional fabrication process using the powder bed fusion method of the present invention will be described below with reference to FIG.

[0016] In a first step, the stage 2 of the bath 1 in which the object is formed is lowered.

[0017] In the second step, the stage 4 of the tank 3 (hereinafter sometimes referred to as the supply tank), which is filled in advance with the material powder P to be supplied to the tank 1 in which the molded object is formed, is raised to a height that allows the supply of a sufficient amount of material powder P to fill the tank 1 with a predetermined stack height. Then, the recoater 5 is moved from the left end of the supply tank 3 to the right end of the tank 1, and the material powder P is stacked in the tank 1. The direction parallel to the movement of the recoater 5 is the X direction, and the direction perpendicular to the movement direction of the recoater 5 on the powder surface of the material powder P is the Y direction. Reference numeral 7 indicates a coordinate system representing the X direction, Y direction, and Z direction. Reference numeral 8 indicates the surface direction in which the material powder is stacked, and reference numeral 9 indicates the height direction in which the material powder is stacked.

[0018] In the third step, the material powder P filled in the tank 1 to a predetermined stacking height in the second step is given thermal energy 6 capable of melting, and selectively melted and sintered according to the modeling data. Reference numeral 11 indicates the height at which the material powder is stacked in advance (hereinafter, sometimes referred to as the preliminary stacking height) before the target three-dimensional object is selectively melted and sintered. Examples of the selective melting and sintering method include a selective laser sintering method in which a laser is irradiated onto a shape corresponding to the cross-sectional shape of the object to be modeled, and a selective absorption (or suppression) sintering method in which a resin powder is bonded using electromagnetic radiation.

[0019] In the powder bed fusion method, the above first to third steps are repeated to obtain a three-dimensional object 10, and the material powder remaining in the tank 1 is subjected to a thermal load at a temperature above the crystallization temperature and below the melting point.

[0020] In the method for producing a three-dimensional object of the present invention, the temperature of the top powder layer of the powder bed is 200° C. or less. By keeping the temperature of the top powder layer of the powder bed at 200° C. or less, it is possible to suppress coloration of the three-dimensional object, thermal deterioration of the polymer powder composition, and thermal load on the three-dimensional modeling device. The temperature of the top powder layer of the powder bed is preferably 199° C. or less, more preferably 198° C. or less, even more preferably 197.5° C. or less, particularly preferably 197° C. or less, and extremely preferably 195° C. or less. In addition, the lower limit is preferably 185° C. or more, more preferably 188° C. or more, even more preferably 190° C. or more, and particularly preferably 192° C. or more, in terms of not causing warping during three-dimensional modeling.

[0021] The powder bed top powder layer temperature in the present invention refers to the temperature of the tank 1 in which the molded object is formed, and particularly refers to the measured value of the upper surface temperature of the material powder P filled in the tank 1. The method for measuring the powder bed top powder layer temperature is not particularly limited, and it can be measured, for example, by an infrared sensor. In a three-dimensional molding process, the powder bed temperature is generally raised to the molding temperature while stacking the material powder, but the powder bed top powder layer temperature in the present invention refers to the upper surface temperature during molding that is being selectively melted and sintered, and the temperature of the hottest part among the parts that can be measured in terms of the device configuration, other than the parts that are being selectively melted and sintered.

[0022] In the present invention, the temperature of the polymer powder composition supplied to the powder bed is preferably 140°C or higher. If the temperature of the polymer powder composition supplied to the powder bed is low, the temperature of the top powder layer of the powder bed will be lowered for each lamination, the time for the temperature of the top powder layer of the powder bed to return to the specified temperature will be longer, and the temperature of the selectively melt-sintered part will be lowered, causing warping. Therefore, 150°C or higher is more preferable, 160°C or higher is even more preferable, 165°C or higher is particularly preferable, and 170°C or higher is extremely preferable. The upper limit is preferably 195°C or lower, more preferably 190°C or lower, more preferably 185°C or lower, particularly preferably 182°C or lower, and extremely preferably 180°C or lower, in that stress is applied when the polymer powder composition is supplied to the powder bed, and therefore it is preferable to set the temperature lower than the top powder layer temperature of the powder bed to suppress thermal deterioration of the polymer powder composition.

[0023] The temperature of the polymer powder composition supplied to the powder bed in the present invention refers to the temperature of the supply tank 3, and particularly refers to the upper surface temperature of the material powder P filled in the supply tank 3. There is no particular limitation on the method for measuring this upper surface temperature, and it can be measured, for example, by an infrared sensor. Furthermore, when the temperature of the polymer powder composition supplied to the powder bed is changed during the three-dimensional modeling process, the temperature refers to the maximum temperature.

[0024] In three-dimensional modeling by powder bed fusion bonding, it is preferable to provide a pre-lamination in order to improve the heat retention of the three-dimensional model and suppress warping. In the present invention, the pre-lamination height refers to the height at which the material powder is laminated in advance before the target three-dimensional model is selectively melt-sintered. The three-dimensional model may be placed between the pre-laminations in order to further improve the heat retention.

[0025] In the present invention, the pre-stacking height is preferably 15 mm or more. By setting the pre-stacking height to 15 mm or more, the heat retention of the three-dimensional object is improved, and a three-dimensional object with a high melting point can be obtained without warping even if the temperature of the uppermost powder layer of the powder bed is 200° C. or less, which is preferable. The pre-stacking height is more preferably 18 mm or more, and even more preferably 20 mm or more. In addition, the upper limit is preferably 40 mm or less, more preferably 35 mm or less, and even more preferably 30 mm or less, in order to reduce the amount of material powder that does not become the three-dimensional object.

[0026] In the method for producing a three-dimensional object of the present invention, a polymer powder composition is used that is composed of a polymer having a melting point of 200°C or higher and suitable for producing a three-dimensional object by a powder bed fusion method. By having a melting point of 200°C or higher, a three-dimensional object having excellent heat resistance can be obtained. The melting point of the polymer constituting the polymer powder composition is preferably 202°C or higher, more preferably 205°C or higher, even more preferably 210°C or higher, particularly preferably 213°C or higher, and particularly preferably 215°C or higher. The upper limit is preferably 250°C or lower, more preferably 240°C or lower, even more preferably 235°C or lower, and particularly preferably 230°C or lower, in that warping is unlikely to occur when three-dimensionally modeled at a temperature of 200°C or lower.

[0027] The melting point of the polymer constituting the polymer powder composition of the present invention is defined as the apex of the endothermic peak observed when the polymer powder composition is heated in a nitrogen atmosphere from 30° C. at a rate of 20° C. / min to a temperature 30° C. higher than the end of the melting peak, using a DSC method.

[0028] In the present invention, the polymer constituting the polymer powder composition preferably contains polyester, polyamide, polyphenylene sulfide, polyether ether ketone, polyamideimide, polytetrafluoroethylene, or a mixture thereof. Polyester, polyamide, polyphenylene sulfide, and polyether ether ketone are more preferable in terms of suppressing warping of the resulting three-dimensionally molded object, and among these, polyamide is particularly preferable in terms of its high effect of lowering the temperature of the uppermost powder layer during molding. Any polyamide may be used as long as it does not impair the present invention, and specific examples include those containing at least one polyamide selected from polyamide 4, polyamide 6 (polycaproamide), polyamide 9, polyamide 610, polyamide 510, polyamide 66, polyamide 46, polyamide 56, polyamide 1010, polyamide 410, polyamide 510, polyamide 612 (polyhexamethylene dodecamide), polyamide 106, polyamide 126, polyamide 6T (polyhexamethylene terephthalamide), polyamide 10T, and copolymers containing any of these. Among these, polyamide 6, polyamide 11, polyamide 66, polyamide 1010, polyamide 610, polyamide 612, and polyamide 510 are preferred, and polyamide 6, polyamide 610, polyamide 510, and copolymers containing any of these are more preferred, and polyamide 6 is particularly preferred, in that they have excellent heat resistance and are suitable for molding without warping when the temperature of the uppermost powder layer of the powder bed is 200°C or less.

[0029] The polyamide may be copolymerized within a range that does not impair the effects of the present invention. The copolymerizable component may be appropriately selected from elastomer components such as polyolefins and polyalkylene glycols that impart flexibility, and rigid aromatic components that improve heat resistance and strength. A copolymerization component that adjusts the end group may also be used. Such a copolymerization component is not limited as long as it is a component that reacts with the amino group or carboxyl group at the end, and examples of the copolymerization component include monocarboxylic acids such as acetic acid, hexanoic acid, lauric acid, and benzoic acid, dicarboxylic acids such as adipic acid, and monoamines such as hexylamine, octylamine, and aniline.

[0030] In the present invention, the polymer powder composition may contain other additives as long as they do not impair the present invention. Examples of additives include antioxidants and heat stabilizers to suppress thermal deterioration caused by heating during modeling in the powder bed fusion method. Examples of antioxidants and heat stabilizers include hindered phenols, hydroquinones, phosphites and their substitutes, phosphites, hypophosphites, and the like. Other examples include pigments and dyes for coloring, plasticizers for adjusting viscosity, flow aids for improving flowability, antistatic agents for imparting functions, flame retardants, and fillers such as carbon black, silica, titanium dioxide, potassium titanate, glass fibers, glass beads, carbon fibers, and cellulose nanofibers. These can be known substances and may be present either inside or outside the polymer powder composition.

[0031] In addition, in the powder bed fusion method, a molded object is produced from a part of the powder composition used, and a large amount of the powder composition remains. It is important from the viewpoint of cost to reuse the powder composition. To achieve this, it is important not to change the properties of the powder composition during the heating and molding process. Examples of such methods include a method of incorporating a stabilizer such as an antioxidant into the inside of the particles to suppress thermal deterioration, and a method of reducing the end groups of polyamide to suppress molecular weight changes during molding. In addition, when a reinforcing material is incorporated into the powder composition, it is preferable to use a reinforcing material that is not denatured by heat. By appropriately using such adjustments, it tends to be possible to achieve both moldability and reuse.

[0032] In the present invention, the D50 particle size of the polymer powder contained in the polymer powder composition is preferably 1 μm or more and 100 μm or less. By having a D50 particle size of 100 μm or less, the particle size becomes less than the stacking height, and the surface of the obtained molded object becomes smooth, which is preferable. By having a D50 particle size of 1 μm or more, the polymer powder is less likely to adhere to a recoater during molding, and the molding chamber can be heated to the required temperature, which is preferable. The upper limit of the D50 particle size of the polymer powder is more preferably 80 μm or less, even more preferably 60 μm or less, even more preferably 50 μm or less, particularly preferably 40 μm or less, and extremely preferably 30 μm or less. The lower limit is more preferably 5 μm or more, even more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 20 μm or more. If D50 is less than the above-mentioned preferable upper limit, the surface roughness of the obtained molded object tends to be smaller. Furthermore, if D50 is equal to or less than the above-mentioned preferable upper limit, the molded object tends to be less likely to warp even if the filler ratio in the polymer powder composition is small. Also, if the D50 particle size is equal to or more than the above-mentioned lower limit, the flowability of the polymer powder composition is improved, so that three-dimensional molding can be performed even if the filler ratio in the polymer composition is increased, and the XY shrinkage tends to be small.

[0033] The D50 particle size of the polymer powder contained in the polymer powder composition is the particle size (D50 particle size) at which the cumulative frequency from the small particle size side of the particle size distribution measured by a laser diffraction particle size distribution meter is 50%.

[0034] The particle size distribution of the polymer powder is not limited as long as it does not impair the present invention, but is preferably less than 5.0, as expressed by D90 / D10, which is the ratio of D90 to D10 in the particle size distribution. A narrower particle size distribution is preferable because it eliminates differences in melting properties during molding due to differences in particle size, and also makes it easier for the reinforcing material to be uniformly dispersed, resulting in a molded product with a smooth surface. Therefore, D90 / D10 is more preferably less than 4.0, even more preferably less than 3.0, and particularly preferably less than 2.0. The lower limit is theoretically 1.0.

[0035] D90 / D10, which indicates the particle size distribution of the polymer powder in the present invention, is the value obtained by dividing the particle size (D90) at which the cumulative frequency from the small particle size side of the particle size distribution measured by the above-mentioned laser diffraction particle size distribution meter is 90% by the particle size (D10) at which the cumulative frequency from the small particle size side is 10%.

[0036] As long as the shape of the polymer powder does not impair the present invention, it does not matter whether it is spherical or amorphous. The closer the shape is to a perfect sphere, the more the fluidity of the powder composition improves and molding can be performed at a lower temperature, so the sphericity indicating the sphericity of the polymer particles is preferably 70 to 100. In addition, in order to improve the quality, particularly the surface smoothness, of a three-dimensional object, the sphericity is more preferably 80 to 100, even more preferably 85 to 100, even more preferably 90 to 100, particularly preferably 95 to 100, and extremely preferably 97 to 100.

[0037] The sphericity of the polymer powder is determined by observing 30 particles randomly from a scanning electron microscope photograph and judging from the ratio of the minor axis to the major axis.

[0038] The weight average molecular weight of the polymer is preferably in the range of 10,000 to 1,000,000. Since the additive manufacturing temperature can be reduced as the weight average molecular weight is higher, the lower limit is preferably 20,000 or more, more preferably 30,000 or more, even more preferably 40,000 or more, and particularly preferably 45,000 or more. If the molecular weight is too high, the viscosity becomes high, which deteriorates the reduction of the additive manufacturing temperature and the recovery of the powder composition, so the upper limit is preferably 500,000 or less, more preferably 200,000 or less, even more preferably 100,000 or less, and particularly preferably 80,000 or less.

[0039] The weight average molecular weight of the polymer constituting the polymer powder refers to a value obtained by measuring the weight average molecular weight by gel permeation chromatography using hexafluoroisopropanol as a solvent and converting it into polymethyl methacrylate.

[0040] The method for producing the polymer powder is not particularly limited, but preferably, the method described in International Publication No. 2018 / 207728 previously disclosed by the present inventors, in which a polyamide monomer is polymerized in the presence of a polymer that is incompatible with polyamide at a temperature higher than the crystallization temperature of the polyamide, and the polyamide powder is then washed and dried to produce the polymer powder, can be used because this method reduces impurities contained in the polyamide powder.

[0041] The polymer powder composition of the present invention preferably contains 10% by mass or more and 80% by mass or less of the reinforcing material based on the total weight of the polymer powder composition. The upper limit of the blending amount is more preferably 70% by mass or less, even more preferably 60% by mass or less, and particularly preferably 50% by mass or less, in terms of not inhibiting the melt sintering of the polymer and reducing the surface roughness of the resulting molded object. The lower limit of the blending amount is more preferably 20% by mass or more, even more preferably 25% by mass or more, particularly preferably 30% by mass or more, and extremely preferably 35% by mass or more, in terms of suppressing shrinkage, particularly on the XY plane, and mechanically suppressing warpage of a three-dimensional molded object, particularly when molded at a low temperature.

[0042] Examples of such reinforcing materials include glass-based fillers such as glass fiber, glass beads, glass flakes, and expanded glass beads; nepheline syenite fine powder, calcined clays such as montmorillonite and bentonite; clays (aluminum silicate powders) such as silane-modified clay; silicic acid-containing compounds such as talc, diatomaceous earth, and silica sand; crushed natural minerals such as pumice powder, pumice balloons, slate powder, and mica powder; minerals such as barium sulfate, lithopone, calcium sulfate, molybdenum disulfide, and graphite; silicas (silicon dioxides) such as fused silica, crystalline silica, and amorphous silica; alumina (aluminum oxide); and alumina colloids ( Examples of the reinforcing materials include alumina such as alumina sol and alumina white, calcium carbonate such as light calcium carbonate, heavy calcium carbonate, finely powdered calcium carbonate, and special calcium carbonate-based fillers, fly ash spheres, volcanic glass hollow bodies, synthetic inorganic hollow bodies, potassium titanate monocrystal, potassium titanate fiber, carbon fiber, carbon nanotubes, carbon hollow spheres, fullerene, anthracite powder, cellulose nanofibers, artificial cryolite, titanium oxide, magnesium oxide, basic magnesium carbonate, dolomite, calcium sulfite, mica, asbestos, calcium silicate, molybdenum sulfide, boron fiber, and silicon carbide fiber. Glass-based fillers, minerals, and carbon fibers are preferred because they are hard and have a large effect of improving strength, and glass-based fillers are more preferred because they have a narrow particle size distribution and fiber size distribution. These reinforcing materials can be used alone or in combination of two or more types.

[0043] Examples of glass-based fillers preferably used in the present invention include glass fibers, glass beads, glass flakes, and foamed glass beads, but glass fibers, glass beads, or a mixture thereof are more preferred because they can impart a high elastic modulus to the three-dimensional object. Among these, glass fibers or a mixture of glass fibers and glass beads are particularly preferred because they can suppress warping of a three-dimensional object having a polymer melting point of 200°C or higher when the temperature of the top powder layer of the powder bed is 200°C or lower. Furthermore, glass fibers are significantly preferred because they impart high strength to the three-dimensional object. The glass fibers may have a circular or flat cross section.

[0044] The reinforcing material preferably used in the present invention has an average major axis of 3 μm or more and 120 μm or less. The upper limit is more preferably 100 μm or less, more preferably 80 μm or less, particularly preferably 50 μm or less, and extremely preferably 40 μm or less, because the filling property of the polymer powder composition is improved when modeled at a low temperature of 200 ° C. or less, the density change when changing from the polymer powder composition state to a three-dimensional model is small, and warping can be suppressed, and the flowability of the polymer powder composition is improved and the surface roughness of the obtained model tends to be small. The lower limit is more preferably 10 μm or more, more preferably 15 μm, particularly preferably 20 μm or more, and extremely preferably 25 μm or more, because a mechanical warping suppression effect is expressed by suppressing shrinkage on the XY plane.

[0045] The shape factor of the reinforcing material preferably used in the present invention is expressed as average major axis / average minor axis, and is preferably 2 to 12. The upper limit is more preferably 10 or less, still more preferably 8 or less, particularly preferably 7 or less, and extremely preferably 6 or less, from the viewpoints that the orientation of the reinforcing material in the X direction is weakened and the proportion of the reinforcing material facing the Y direction is increased, thereby suppressing shrinkage in the Y direction and making warping in the Y direction less likely, and that the flowability of the polymer powder composition is improved and the surface roughness of the obtained molded object tends to be small. The lower limit is more preferably 2.5 or more, particularly preferably 3 or more, from the viewpoints of suppressing warping and increasing the strength of the obtained molded object.

[0046] The major axis of the reinforcing material preferably used in the present invention is preferably 0.1 or more and 4.0 or less, in terms of (major axis of reinforcing material) / (D50 particle diameter of polymer particles). The upper limit is more preferably 3.0 or less, and even more preferably 2.0 or less. The lower limit is more preferably 0.5 or more. When (major axis of reinforcing material) / (D50 particle diameter of polymer particles) is within the above range, that is, when the major axis of the reinforcing material and the D50 particle diameter of the polymer particles are close to each other, the flowability of the polymer powder composition is improved, and the surface roughness of the obtained shaped object tends to be reduced.

[0047] In the present invention, the average major axis and the average minor axis of the reinforcing material are the number average values ​​of the major axis and minor axis of 100 randomly selected fibers or particles in a photograph of the reinforcing material taken with a scanning electron microscope. The major axis is the diameter at which the distance between the parallel lines is maximum when the image of the particle is sandwiched between two parallel lines, and the minor axis is the diameter at which the distance between the parallel lines is minimum when the image of the particle is sandwiched between two parallel lines in a direction perpendicular to the major axis. When measuring the average major axis and the average minor axis of the reinforcing material, the major axis and minor axis may be measured by selecting the reinforcing material from a scanning electron microscope photograph of the powder composition.

[0048] The reinforcing material preferably used in the present invention has an apparent density / tap density of 0.50 or more and 1.00 or less. The apparent density / tap density of 0.50 or more is preferable because the reinforcing material itself has excellent filling property and flowability, and the dispersibility when made into a polymer powder composition is improved, and it is possible to uniformly exhibit a mechanical warpage suppression effect in the polymer powder composition. The apparent density / tap density is more preferably 0.55 or more, even more preferably 0.60 or more, and particularly preferably 0.62 or more. The upper limit is more preferably 0.90 or less, more preferably 0.85 or less, and particularly preferably 0.80 or less, in terms of the shape factor that suppresses warpage.

[0049] The apparent density of the reinforcing material refers to the mass per unit volume when the reinforcing material powder is filled in a container. The apparent density is measured according to the Japanese Industrial Standards (JIS) K 7365 (1999) "Determination of the apparent density of a material that can be poured from a specified funnel."

[0050] The tap density of a reinforcing material indicates the mass per unit volume when the reinforcing material powder is gently filled into a container and then tapped to pack tightly, and is measured in accordance with the Japanese Industrial Standards (JIS) K 7370 (2000) "Determination of packed apparent bulk density."

[0051] To the extent that the effect of the present invention is not impaired, it is possible to use a reinforcing material that has been subjected to a surface treatment in order to improve the adhesion between the reinforcing material and the polymer. Examples of such surface treatments include silane coupling agents such as aminosilane, epoxysilane, and acrylicsilane. These surface treatment agents may be fixed on the surface of the reinforcing material by a coupling reaction, or may cover the surface of the reinforcing material, but in terms of recycling the material powder used in three-dimensional modeling, those that have been fixed by a coupling reaction are preferred in that they are not easily modified by heat or the like. In particular, by using a reinforcing material in which an aminosilane coupling agent has been fixed by a coupling reaction, the adhesion between the reinforcing material and the polymer can be improved, and the mechanical strength of the modeled object tends to be further improved.

[0052] In the present invention, the reinforcing material may be dry-blended with the polymer particles or may be contained inside the polymer particles. However, it is preferable to dry-blend the reinforcing material, since this provides an orientation suitable for achieving mechanical warpage suppression during recoating.

[0053] In order to improve the flowability of the polymer powder composition, it is preferable to include a flow aid, so long as the effects of the present invention are not impaired. The flow aid refers to a substance that suppresses the aggregation of powder due to the adhesive force between powders. By including such a flow aid, the flowability of the powder composition can be improved, that is, the angle of repose, which is an index of flowability described later, can be improved to a desired range, and defects that cause deterioration of mechanical properties tend to be reduced and the appearance of the resulting molded product can be improved.

[0054] Examples of such flow aids include silica (silicon dioxide) such as fused silica, crystalline silica, and amorphous silica, alumina (aluminum oxide), alumina colloid (alumina sol), and alumina white, calcium carbonate such as light calcium carbonate, heavy calcium carbonate, finely powdered calcium carbonate, and special calcium carbonate-based fillers, titanium oxide, magnesium oxide, basic magnesium carbonate, potassium titanate fiber, boron fiber, and silicon carbide fiber. More preferred are silica, alumina, calcium carbonate powder, and titanium oxide. Particularly preferred is silica, which is hard and can contribute to improving strength and fluidity.

[0055] Commercially available examples of such silica include the fumed silica "AEROSIL" (registered trademark) series manufactured by Nippon Aerosil Co., Ltd., the dry silica "Reolosil" (registered trademark) series manufactured by Tokuyama Corporation, and the sol-gel silica powder X-24 series manufactured by Shin-Etsu Chemical Co., Ltd.

[0056] The D50 particle size of the flow aid is preferably 20 nm or more and 3000 nm or less. The upper limit of the D50 particle size of the flow aid is more preferably 2000 nm, more preferably 1000 nm, particularly preferably 500 nm, very preferably 300 nm, and most preferably 200 nm. The lower limit is more preferably 30 nm, more preferably 50 nm, particularly preferably 100 nm, very preferably 120 nm, and most preferably 140 nm. If the D50 particle size of the flow aid is within the above range, the flowability of the powder composition is improved and the flow aid tends to be uniformly dispersed in the powder composition.

[0057] The D50 particle size of such a flow aid is the particle size at which the cumulative frequency from the small particle size side of the particle size distribution measured by a laser diffraction particle size distribution meter is 50%, or the median of the measured length values ​​of 100 powder particles randomly observed in a photograph taken by a scanning electron microscope.

[0058] The blending amount of the flow aid is preferably 0.01% by mass or more and 2.0% by mass or less based on the total weight of the polymer powder composition. The upper limit of the blending amount is more preferably 1.5% by mass or less, even more preferably 1.0% by mass or less, particularly preferably 0.8% by mass or less, and extremely preferably 0.7% by mass or less. The lower limit of the blending amount is more preferably 0.02% by mass or more, even more preferably 0.03% by mass or more, and particularly preferably 0.04% by mass or more. If the blending amount of the flow aid is equal to or more than the lower limit, the flowability of the polymer powder composition is further improved, and the filling property when molded is increased, so that voids that are defects in mechanical properties are less likely to occur, and the molded product obtained tends to have high strength. If the blending amount of the flow aid is equal to or less than the upper limit, the surface of the polymer particles is not covered with the flow aid, which prevents sintering, and the molded product obtained tends to have high strength.

[0059] Any known measurement method can be used as an index of the flowability of the polymer powder composition of the present invention. A specific example is the angle of repose, which is preferably 55 degrees or less. More preferably, it is 50 degrees or less, even more preferably 45 degrees or less, even more preferably 40 degrees or less, and particularly preferably 35 degrees or less. The lower limit is usually 30 degrees or more. By having the angle of repose within the above preferred range, the flowability of the polymer powder composition is further improved, and the filling property when molded is increased, so that voids that are defects in mechanical properties are less likely to occur, and the obtained molded object tends to exhibit high strength. Furthermore, the surface roughness of the obtained molded object tends to be small.

[0060] The yellowness of the polymer powder composition used in the present invention is preferably 10 or less, more preferably 9 or less, even more preferably 8 or less, and particularly preferably 7 or less. By having the yellowness be equal to or less than the above upper limit, a 3D object with high saturation can be obtained when coloring the object, and the design can be improved when used in the final product application. The lower limit is preferably -5 or more, more preferably -3 or more, even more preferably -1 or more, and particularly preferably 0 or more, since a too low yellowness results in a bluish tinge.

[0061] The yellowness of the polymer powder composition of the present invention is the b* value measured by placing about 6 g of the powder in a round quartz cell with a diameter of 35 mm and measuring it using a spectrophotometer (SE2000) manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS Z8722 (2009) and JIS Z8781-4 (2013).

[0062] Furthermore, the lightness of the polymer powder composition before three-dimensional modeling used in the present invention is preferably at least 20, more preferably at least 50, even more preferably at least 70, particularly preferably at least 80, and most preferably at least 90. When the lightness of the polymer powder composition is at least the above lower limit, the lightness of the resulting three-dimensionally modeled object is increased and color turbidity is reduced when the three-dimensionally modeled object is colored, thereby improving the designability when used in final products.

[0063] In the method for producing a three-dimensional object of the present invention, a polymer powder composition composed of a polymer having a melting point of 200 ° C. or more is three-dimensionally produced at a temperature of the top powder layer of the powder bed of 200 ° C. or less, thereby suppressing the change in color of the polymer powder composition before and after three-dimensional modeling. When the lightness L(1) of the polymer powder composition before three-dimensional modeling and the lightness L(2) of the polymer powder composition remaining in the tank 1 after three-dimensional modeling are taken as the lightness, it is preferable that L(2) / L(1) is 0.85 or more and 1.05 or less. The lower limit is more preferably 0.90 or more, more preferably 0.93 or more, and particularly preferably 0.95 or more, in that the color of the three-dimensional modeled object and the polymer powder composition are more consistent. The upper limit is more preferably 1.03 or less, and even more preferably 1.02 or less, in that the lightness increases before and after three-dimensional modeling when the lightness L(1) before three-dimensional modeling is small, but the smaller the color change, the more stable the quality of the three-dimensional modeled object can be obtained.

[0064] The lightness L(1) and L(2) of the polymer powder composition are the L* values ​​measured by placing approximately 6 g of powder in a round quartz cell with a diameter of 35 mm and measuring the L* value using a spectrophotometer (SE2000) manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS Z8722 (2009) and JIS Z8781-4 (2013). The L* value of the powder before three-dimensional modeling is L(1), and the L* value of the powder after modeling is L(2).

[0065] In the present invention, since the temperature of the uppermost powder layer of the powder bed during shaping can be lowered, it is possible to suppress the thermal history of the shaped object. Accordingly, an increase in the weight-average molecular weight of the polymer powder and the polymer constituting the shaped object is suppressed, and the weight-average molecular weight of the polymer constituting the shaped object is preferably 10,000 to 100,000. The lower the upper limit of the weight-average molecular weight, the more preferable it is because it suppresses coloring due to the thermal history of the shaped object and fusion of the powder composition, and improves the recoverability of the powder composition. The upper limit is more preferably 90,000 or less, and particularly preferably 80,000 or less. From the viewpoint of the mechanical properties of the shaped object, the lower limit is more preferably 30,000 or more, and particularly preferably 40,000 or more.

[0066] The recovery of the powder composition indicates the recovery rate of the powder composition in the non-laser irradiated portion after additive manufacturing. The higher the recovery rate, the shorter the working time for recovering the powder composition can be, and the more the amount of the powder composition that can be reused is, which is preferable from the viewpoint of economic efficiency. The recovery rate is preferably 50 wt% or more, more preferably 80 wt% or more.

[0067] The recovery rate is calculated by collecting 100 g of the powder remaining in the modeling apparatus after additive manufacturing is completed, measuring the weight of the powder composition that passed through a 500 μm sieve, and calculating the ratio of the weight of the powder composition that passed through the sieve to the weight of the charged powder.

[0068] The three-dimensional structure of the present invention will be described in detail below.

[0069] The three-dimensional object of the present invention is a three-dimensional object obtained by using a polymer powder composition that produces a test piece 80 mm long and 4 mm thick, with the 80 mm length direction perpendicular to the direction of recoater movement and the 4 mm thickness direction being the height direction in which the material powder is layered, and the warp of the test piece is 1.5 mm / 10 cm or less. The use of a polymer powder composition that produces a test piece with a warp of the above upper limit or less means that the warp of the resulting three-dimensional object is small and the three-dimensional object maintains a shape close to the design. It is more preferable to use a polymer powder that produces a test piece with a warp of 1.2 mm / 10 cm or less.

[0070] In the present invention, the method for measuring the warpage of the test specimen is to place the test specimen on a horizontal surface in an upward convex state, insert a precision taper gauge into the gap between the horizontal surface and the test specimen, measure the height of the gap, and convert the value per 10 cm of the test specimen length to the amount of warpage. The arithmetic average of the amounts of warpage of the six test specimens is then calculated.

[0071] The three-dimensional object of the present invention has a melting point of 200°C or higher for the polymer constituting the three-dimensional object. The melting point of 200°C or higher allows the three-dimensional object to be used for functional prototyping and final product applications as a three-dimensional object with excellent heat resistance. The melting point of the polymer constituting the three-dimensional object is preferably 202°C or higher, more preferably 205°C or higher, even more preferably 210°C or higher, particularly preferably 213°C or higher, and extremely preferably 215°C or higher. The upper limit is preferably 250°C or lower, more preferably 240°C or lower, even more preferably 235°C or lower, and particularly preferably 230°C or lower, in that warping is unlikely to occur when the three-dimensional object is three-dimensionally shaped at a temperature of 200°C or lower.

[0072] The melting point of the polymer constituting the three-dimensional object of the present invention is defined as the apex of the endothermic peak observed when a sample piece cut from the edge of the three-dimensional object is measured using a DSC method under conditions in which the sample piece is heated in a nitrogen atmosphere from 30°C at a rate of 20°C / min to a temperature 30°C higher than the end of the melting peak.

[0073] The three-dimensional object of the present invention has a yellowness of 10 or less. By having a yellowness of 10 or less, a highly saturated object can be obtained when coloring the three-dimensional object, and the design can be improved when used in final products. The yellowness of the three-dimensional object is more preferably 9 or less, even more preferably 8 or less, and particularly preferably 7 or less. The lower limit is preferably -5 or more, more preferably -3 or more, even more preferably -1 or more, and particularly preferably 0 or more, since a too low yellowness results in a bluish tinge.

[0074] The yellowness of the three-dimensional object of the present invention is the b* value measured on a flat surface of the three-dimensional object in accordance with JIS Z8722 (2009) and JIS Z8781-4 (2013) using a spectrophotometer (SE2000) manufactured by Nippon Denshoku Industries Co., Ltd.

[0075] Furthermore, from the viewpoint of reducing color turbidity when coloring the three-dimensional object of the present invention, the brightness of the three-dimensional object is preferably 20 or more, more preferably 50 or more, even more preferably 70 or more, particularly preferably 80 or more, and most preferably 90 or more.

[0076] The lightness of the three-dimensional object of the present invention is the L* value measured on a flat surface of the three-dimensional object in accordance with JIS Z8722 (2009) and JIS Z8781-4 (2013) using a spectrophotometer (SE2000) manufactured by Nippon Denshoku Industries Co., Ltd.

[0077] In addition, in three-dimensional modeling, the powder is filled and then melted and sintered under normal pressure to produce a model, which usually involves density changes due to shrinkage. Therefore, in order to obtain highly accurate dimensions of the three-dimensional model based on the desired modeling data, it is preferable for the three-dimensional model to have a moderate amount of pores inside. The proportion and shape of the pores present in the three-dimensional model of the present invention can be observed by X-ray CT.

[0078] The three-dimensional object of the present invention is imaged by X-ray CT, and the ratio of the portion observed as a void to the entire volume of the object can be expressed as the void ratio. The void ratio observed by X-ray CT measurement of the three-dimensional object of the present invention is preferably 0.1 volume % or more and 10 volume % or less. If the void ratio is too small, the entire object will shrink relative to the modeling data, so the lower limit of the void ratio is more preferably 0.2 volume % or more, even more preferably 0.3 volume % or more, and particularly preferably 0.5 volume % or more. In addition, the upper limit is more preferably 5.0 volume % or less, even more preferably 4.0 volume % or less, and particularly preferably 3.0 volume % or less, because a large number of voids can cause a decrease in strength.

[0079] The size of each independent hole observed as a void when the three-dimensional object of the present invention is imaged by X-ray CT can be expressed as a sphere-equivalent diameter. The average sphere-equivalent diameter of the voids observed by X-ray CT measurement of the three-dimensional object of the present invention is preferably 1 μm or more and 100 μm or less. In the case of melt molding not using a three-dimensional molding process, the average sphere-equivalent diameter of the voids is usually designed to be less than 1 μm, and in the case of intentionally forming voids such as foam molding, the average sphere-equivalent diameter of the voids is usually more than 100 μm. As described above, in three-dimensional molding under normal pressure, a certain amount of voids are generated, so the lower limit is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. The upper limit is preferably 80 μm or less, more preferably 60 μm or less, and even more preferably 50 μm or less, because large voids become defects and cause a decrease in the strength of the molded object.

[0080] In the present invention, the porosity and the average equivalent spherical diameter of the pores of the three-dimensional object are obtained by imaging the three-dimensional object with an accuracy of 5 μm pixel size by X-ray CT, labeling the pores in the observed image, calculating the equivalent spherical diameter, which is the diameter of each independent pore when it is treated as a sphere, and averaging the average of the labeling results. The porosity is also obtained by dividing the volume of the labeled pores by the total volume of the pores filled in the part of the object in the observed image, and multiplying the result by 100.

[0081] The heat distortion temperature of the three-dimensional object of the present invention is preferably 160°C or higher. The higher the heat distortion temperature, the less the object is likely to deform in a high-temperature environment, making it possible to use the object in tests under more severe environments or as a final product. Therefore, the lower limit is more preferably 170°C or higher, even more preferably 180°C or higher, and particularly preferably 185°C or higher. The upper limit is equal to or lower than the melting point of the polymer constituting the three-dimensional object.

[0082] In the present invention, the heat distortion temperature is the value of the deflection temperature under load measured at a load of 0.45 MPa in accordance with the Japanese Industrial Standards (JIS) K7191-1 (2015) "Plastics - Determination of deflection temperature under load".

[0083] The surface roughness of the three-dimensional object of the present invention is preferably 20 μm or less. Since the smaller the surface roughness, the higher the quality and the better the adhesion of the joints between the three-dimensional objects, the surface roughness is more preferably 18 μm or less, even more preferably 15 μm or less, even more preferably 12 μm or less, particularly preferably 10 μm or less, and extremely preferably 8 μm or less. The lower limit is not particularly limited, and a smaller one is preferable, but the lower limit is usually 1 μm. The surface roughness of the three-dimensional object is a value obtained by observing the surface of the object with an optical microscope, three-dimensionally imaging the unevenness of the object surface in an automatic synthesis mode, obtaining a cross-sectional height profile over a length of 1 mm or more, and calculating the surface roughness Ra by the arithmetic average.

[0084] The flexural modulus in the X direction of the shaped object of the present invention is appropriately adjusted depending on the polymer powder and reinforcing material used, but is preferably 2000 MPa or more. The higher the elastic modulus, the higher the rigidity of the shaped object and the less likely it is to deform, so the flexural modulus in the X direction of the shaped object is preferably 2500 MPa or more, more preferably 3000 MPa or more, even more preferably 4000 MPa or more, and particularly preferably 5000 MPa or more. There is no particular upper limit, but generally, if the elastic modulus becomes too large, it tends to become brittle and have low strength, so it is preferably 20000 MPa or less, more preferably 15000 MPa or less, even more preferably 12000 MPa or less, and particularly preferably 10000 MPa or less.

[0085] In the present invention, the bending modulus in the X direction can be measured by preparing a test piece having a width of 10 mm, a length of 80 mm, and a thickness of 4 mm so that the thickness direction of 4 mm is the Z direction and the length direction of 80 mm is the X direction, and performing a three-point bending test in accordance with JIS K7171 (2016) under the conditions of a support distance of 64 mm and a test speed of 2 mm / min. The measurement temperature is room temperature (23°C), the number of measurements is n=10, and the average value is the bending modulus in the X direction.

[0086] Compared to normal melt molding, three-dimensional objects are obtained by crystallization in a process of lowering the temperature at normal pressure at a slow rate, so the state of the crystals is different from that of normal melt molding, but it is difficult to express this as a feature of the product, so they are limited by the manufacturing method, that is, three-dimensional molding, preferably powder bed fusion bonding. It is known that with normal melt molding, molded products with high melting points and little coloring can be obtained by diligent study by those skilled in the art according to the structure of the mold, but in three-dimensional molding that can mold complex shapes, it has not been possible to obtain molded products that have both a high melting point and coloring suppression, and this has only become possible with the present invention. EXAMPLES

[0087] The present invention will now be described with reference to examples.

[0088] (1) Measurement of the D50 particle size of the polymer powder contained in the polymer powder composition A dispersion of about 100 mg of a polymer powder composition dispersed in about 5 mL of deionized water was added to a laser diffraction particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Nikkiso Co., Ltd. until a measurable concentration was reached, and ultrasonic dispersion was performed for 60 seconds at 30 W in the analyzer, and the particle size at which the cumulative frequency from the small particle size side of the particle size distribution measured in a measurement time of 10 seconds is 50% was defined as the D50 particle size. The refractive index during measurement was 1.52, and the refractive index of the medium (deionized water) was 1.333.

[0089] (2) Sphericity of the polymer powder contained in the polymer powder composition The sphericity of the polymer particles contained in the polymer powder composition was determined by photographing the polymer powder composition with a scanning electron microscope (JSM-6301NF) manufactured by JEOL Ltd., randomly observing 30 polymer particles from the photograph, and calculating the sphericity as a percentage from the ratio of their minor axis to their major axis.

[0090] (3) Measurement of the average major axis and minor axis of the reinforcement The reinforcing materials were observed using a scanning electron microscope (JSM-6301NF) manufactured by JEOL Ltd., and the average values ​​of the major and minor axes of 100 reinforcing materials randomly selected from the photograph were taken as the average major axis diameter and the average minor axis diameter.

[0091] (4) Apparent density and tapped density of reinforcement The apparent density of the reinforcement material was measured according to the Japanese Industrial Standards (JIS) Z 7365 (1999) by pouring 50 g of reinforcement material into a funnel and dropping it 100 cm 3 The volume was read and the weight of the reinforcement divided by the volume. The tap density of the reinforcement was calculated by dropping 50 g of the reinforcement into a funnel 100 cm from the funnel in accordance with the Japanese Industrial Standards (JIS) Z 7370 (2000). 3 The weight of the reinforcing material was divided by the volume, and the weight of the reinforcing material was determined as the weight of the reinforcing material.

[0092] (5) Measurement of yellowness b* and lightness L(1) of the polymer powder composition before 3D printing, and lightness L(2) after 3D printing 6 g of the polymer powder composition before three-dimensional modeling was added to a dedicated colorless, transparent, round quartz cell with a diameter of 35 mm, and the cell was filled densely while being vibrated. The b* and L* values ​​obtained by measuring the b* and L* values ​​using a spectrophotometer (SE2000) manufactured by Nippon Denshoku Kogyo Co., Ltd. according to JIS Z8722 (2009) and JIS Z8781-4 (2013) were defined as the b* and L(1) of the polymer powder composition before three-dimensional modeling. Regarding L(2) of the polymer powder composition after three-dimensional modeling, a powder bed fusion type 3D printer (RaFaElII 300-HT) manufactured by Aspect Co., Ltd. was used to perform three-dimensional modeling with a stacking height of 150 mm or more under specified conditions, and the powder remaining in the tank 1 forming the model was used as a polymer powder composition sample after three-dimensional modeling. The L* obtained by measuring the L* was defined as the L(2) of the polymer powder composition after three-dimensional modeling.

[0093] (6) Measurement of yellowness b* and brightness L* of three-dimensional objects A test piece with a width of 10 mm, length of 80 mm, and thickness of 4 mm was produced using a powder bed fusion 3D printer (RaFaElII 300-HT) manufactured by Aspect Corporation, with the thickness direction of 4 mm being the Z direction and the length direction of 80 mm being the X direction. The upper XY surface of the test piece produced in tank 1 after three-dimensional printing was measured for the b* value and L* value (n=3) using a spectrophotometer (SE2000) manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS Z8722 (2009) and JIS Z8781-4 (2013), and the arithmetic mean value was calculated. In addition, the yellowness was evaluated according to the following criteria, and a rank of "A" or "B" was deemed to have passed. A: b value is 7 or less. B: b value is greater than 7 and less than 10. C: b value is greater than 10.

[0094] (7) Determination of warpage of 3D objects in the X direction Using a powder bed fusion 3D printer (RaFaElII 300-HT) manufactured by Aspect Inc., test pieces measuring 10 mm in width, 80 mm in length, and 4 mm in thickness were produced in groups of six, with the 4 mm thickness direction being the Z direction and the 80 mm length direction being the X direction. The test pieces obtained were placed on a horizontal surface in a convex upward state, and a precision taper gauge was inserted into the gap between the horizontal surface and the test piece to measure the height of the gap. The value converted per 10 cm of test piece length was regarded as the amount of warping, and the arithmetic average value was calculated and the amount of warping was evaluated according to the following criteria. A: The amount of warping is less than 0.1mm / 10cm. B: The amount of warping is greater than 0.1mm / 10cm and less than 0.3mm / 10cm. C: The amount of warping is greater than 0.3 mm / 10 cm. If the rank was "A" or "B", the candidate was considered to have passed.

[0095] (8) Determination of warpage of 3D objects in the Y direction Using a powder bed fusion 3D printer (RaFaElII 300-HT) manufactured by Aspect Inc., test pieces measuring 10 mm in width, 80 mm in length, and 4 mm in thickness were produced in groups of six, with the 4 mm thickness direction being the Z direction and the 80 mm length direction being the Y direction. The test pieces obtained were placed on a horizontal surface in a convex upward position, and a precision taper gauge was inserted into the gap between the horizontal surface and the test piece to measure the height of the gap. The value converted per 10 cm of test piece length was regarded as the amount of warping, and the arithmetic average value was calculated and the amount of warping was evaluated according to the following criteria. A: The amount of warping is 1.2mm / 10cm or less. B: The amount of warping is greater than 1.2mm / 10cm and less than 1.5mm / 10cm. C: The amount of warping is greater than 1.5 mm / 10 cm. If the rank was "A" or "B", the candidate was considered to have passed.

[0096] (9) Measurement of XY shrinkage of 3D objects Using a powder bed fusion 3D printer (RaFaElII 300-HT) manufactured by Aspect Corporation, test pieces measuring 10 mm in width, 80 mm in length, and 4 mm in thickness were produced, six of which were in each of two directions, with the 4 mm thickness direction in the Z direction and the 80 mm length direction in the X direction and Y direction, respectively. The dimensions in the width and length directions were measured to the nearest 0.1 mm with a vernier caliper. The area of ​​each test piece in the width and length directions was calculated by multiplying the area in the width and length directions of the three-dimensional data by 800 mm 2 The value obtained by dividing the obtained value by this was regarded as the shrinkage rate, and the arithmetic average value of the 12 test pieces was calculated.

[0097] (10) Measurement of surface roughness of 3D objects A test piece with a width of 10 mm, length of 80 mm, and thickness of 4 mm was produced using a powder bed fusion 3D printer (RaFaElII 300-HT) manufactured by Aspect Corporation, with the 4 mm thickness direction being the Z direction and the 80 mm length direction being the X direction. After 3D printing, the upper XY surface of the test piece produced in tank 1 was observed with an optical microscope, and the unevenness of the surface of the model was three-dimensionally imaged in automatic synthesis mode. After that, a cross-sectional height profile was obtained over a length of 1 mm or more, and the surface roughness Ra was calculated by the arithmetic average.

[0098] (11) Measurement of bending modulus and bending strength of three-dimensional objects The flexural modulus and flexural strength of the three-dimensional model were measured by using a powder bed fusion 3D printer (RaFaElII 300-HT) manufactured by Aspect Inc. to prepare test pieces with a width of 10 mm, length of 80 mm, and thickness of 4 mm, with the thickness direction of 4 mm being the Z direction and the length direction of 80 mm being the X direction or Y direction, and measuring the flexural modulus and flexural strength, respectively, using a Tensilon universal testing machine (TENSIRON TRG-1250) manufactured by A&D Co., Ltd. In accordance with JIS K7171 (2016), a three-point bending test was performed under the conditions of a support distance of 64 mm and a test speed of 2 mm / min to determine the flexural modulus. The flexural strength was the maximum bending stress. The measurement temperature was room temperature (23°C), the number of measurements was n=10, and the average value was calculated. The measurement results of the test piece prepared so that the length direction of 80 mm was the X direction were taken as the flexural modulus and flexural strength in the X direction, and the measurement results of the test piece prepared so that the length direction of 80 mm was the Y direction were taken as the flexural modulus and flexural strength in the Y direction.

[0099] (12) Thermal deformation temperature of three-dimensional objects The thermal distortion temperature of the three-dimensional object was measured by using a powder bed fusion 3D printer (RaFaElII 300-HT) manufactured by Aspect Co., Ltd. to create a test piece with a width of 10 mm, length of 80 mm, and thickness of 4 mm, with the thickness direction of 4 mm being the Z direction and the length direction of 80 mm being the X direction, and using a heat distortion tester (No. 148) manufactured by Yasuda Seiki Seisakusho Co., Ltd., in accordance with JIS K7191-1 (2015), at a load of 0.45 MPa. The number of measurements was n=3, and the average value was calculated.

[0100] (13) Melting point of the polymer constituting the polymer powder composition, and melting point of the polymer constituting the three-dimensional object The melting point of the polymer constituting the polymer powder composition was determined as the apex of the endothermic peak observed when the polymer powder composition was used as a sample and heated in a nitrogen atmosphere from 30° C. to a temperature 30° C. higher than the end of the melting peak at a rate of 20° C. / min using a differential scanning calorimeter (DSCQ20) manufactured by TA Instruments Inc. The melting point of the polymer constituting the three-dimensional object was measured in the same manner using a sample obtained by scraping off a part of the three-dimensional object.

[0101] (14) Weight average molecular weight of polymer particles and polymers constituting three-dimensional objects The weight-average molecular weight of the polymer particles was calculated by gel permeation chromatography in comparison with a calibration curve using polymethyl methacrylate. The measurement sample was prepared by dissolving about 3 mg of the polymer particle powder in about 3 g of hexafluoroisopropanol and filtering out the insoluble matter. The weight-average molecular weight of the polymer constituting the three-dimensional object was measured in the same manner using about 3 mg of the three-dimensional object. Instrument: Waters e-Alliance GPC system Column: Showa Denko HFIP-806M x 2 Mobile phase: 5mmol / L sodium trifluoroacetate / hexafluoroisopropanol Flow rate: 1.0ml / min Temperature: 30℃ Detection: Differential refractometer.

[0102] (15) Recovery of powder composition from non-laser irradiated areas After the additive manufacturing was completed, 100 g of the powder remaining in the modeling device was collected, and the weight of the powder composition that had passed through a 500 μm sieve was measured. The ratio of the weight of the powder composition that had passed through the sieve to the weight of the charged powder was taken as the recovery rate. Evaluation was performed according to the following criteria. A: Recovery rate of 80wt% or more. B: Recovery rate is 50wt% or more but less than 80wt%. C: Recovery rate less than 50 wt%. A~B is pass, C is fail.

[0103] [Production Example 1] Polymer particles (A-1) were produced by the method described in International Publication No. 2018 / 207728. Specifically, 360 g of ε-caprolactam (special grade reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polyamide monomer, 240 g of polyethylene glycol (1st grade polyethylene glycol 6,000, molecular weight 7,700 manufactured by Wako Pure Chemical Industries, Ltd.) as a polymer incompatible with the obtained polyamide, 2.5 g of antioxidant (BASF "IRGANOX" (registered trademark) 1098), and 50 g of deionized water were added to a 3 L autoclave and sealed, and the process of pressurizing with nitrogen to 1 MPa and releasing the pressure to 0.1 MPa was repeated three times, and the inside of the container was replaced with nitrogen, and the pressure was adjusted to 0.1 MPa and the container was sealed. Thereafter, the stirring speed was set to 60 rpm and the temperature was raised to 230 ° C. At this time, the pressure in the system was 1.4 MPa, and stirring was continued at 60 rpm for 3 hours while maintaining the pressure and temperature. Next, the pressure was released at a rate of 0.02 MPa / min, and the internal pressure was set to 0 MPa. After that, the polymerization temperature was set to 210°C, and nitrogen was flowed at a rate of 5 L / min to perform polymerization for 2 hours. Finally, the mixture was discharged into a 2000 g water bath to obtain a slurry. After the slurry was sufficiently homogenized by stirring, it was filtered, and 2000 g of water was added to the filtered product and washed at 80°C. Then, the slurry liquid, from which the coarse matter passed through a 100 μm sieve was removed, was filtered again, and the isolated filtered product was dried at 80°C for 12 hours to produce 300 g of polyamide 6 powder. The D50 particle size of the obtained polyamide powder was 52 μm, the sphericity was 95, and the weight average molecular weight was 54,000.

[0104] [Production Example 2] Polymer particles (A-2) were produced by the method described in WO 2018 / 207728. The polymer particles (A-2) were polyamide 6 powder with a sphericity of 96, a D50 particle size of 35 μm, a melting point of 217° C., and a weight average molecular weight of 45,000.

[0105] [Production Example 3] Polymer particles (A-3) were produced by the method described in WO 2018 / 207728. The polymer particles (A-3) were polyamide 6 powder with a sphericity of 96, a D50 particle size of 21 μm, a melting point of 217° C., and a weight average molecular weight of 45,000.

[0106] [Example 1] 12 kg of polymer particles (A-1) obtained by repeating Production Example 1 was mixed with 8 kg of glass fiber EPG40M-01N (manufactured by Nippon Electric Glass Co., Ltd.) as a reinforcing material. Furthermore, 60 g of trimethylsilylated amorphous silica X-24-9500 (manufactured by Shin-Etsu Chemical Co., Ltd., D50 particle size 170 nm) was added as a flow aid to obtain a polymer powder composition. Using 20 kg of this polymer powder composition, a three-dimensional model was manufactured using a powder bed fusion device (RaFaElII 300-HT) manufactured by Aspect Co., Ltd. The setting conditions were as follows: a 60W CO2 laser was used, the layer height was 0.1 mm, the preliminary layer height was 15 mm, the laser scanning interval was 0.1 mm, the laser scanning speed was 10 m / s, and the laser output was 17 W. The temperature settings were adjusted so that the powder bed top powder layer temperature was 197 ° C, the supply tank temperature was 180 ° C, and the model height was 220 mm. The temperature of the top powder during molding was consistent with the set value. The obtained three-dimensional object had no warping in either the X or Y direction, was white in appearance, and had good quality. The powder composition used, the molding method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0107] [Example 2] A polymer powder composition was prepared in the same manner as in Example 1, except that glass fiber EPG70M-01N (manufactured by Nippon Electric Glass Co., Ltd.) was used as the reinforcing material, and three-dimensional modeling was performed to produce a three-dimensional object. The top powder temperature during modeling was consistent with the set value. The obtained three-dimensional object had no warping in the X direction, only a small warping in the Y direction, a white appearance, and good quality. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0108] [Example 3] A polymer powder composition was prepared in the same manner as in Example 1, except that glass fiber EPG40M-10A (manufactured by Nippon Electric Glass Co., Ltd.) was used as the reinforcing material, and three-dimensional modeling was performed to produce a three-dimensional object. The top powder temperature during modeling was consistent with the set value. The obtained three-dimensional object had no warping in the X direction, only a small warping in the Y direction, a white appearance, and good quality. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0109] [Example 4] Except for changing the blending amount of the polymer particles and the reinforcing material, a polymer powder composition was prepared in the same manner as in Example 1, and three-dimensional modeling was performed to produce a three-dimensional object. The temperature of the top powder during modeling was consistent with the set value. The temperature of the top powder during modeling was consistent with the set value. The temperature of the top powder during modeling was consistent with the set value. The obtained three-dimensional object had no warping in the X direction, only a small warping in the Y direction, a white appearance, and good quality. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0110] [Example 5] A polymer powder composition was prepared in the same manner as in Example 4, except that the modeling temperature was changed, and three-dimensional modeling was performed to produce a three-dimensional object. The top powder temperature during modeling was consistent with the set value. The obtained three-dimensional object had no warping in either the X or Y direction, was slightly yellowed but had a white appearance, and was of good quality. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0111] [Example 6] 14 kg of polymer particles (A-3) was mixed with 6 kg of glass fiber EPG40M-01N (manufactured by Nippon Electric Glass Co., Ltd.) as a reinforcing material. Furthermore, 200 g of trimethylsilylated amorphous silica X-24-9500 (manufactured by Shin-Etsu Chemical Co., Ltd., D50 particle size 170 nm) was added as a flow aid to obtain a polymer powder composition. Using this polymer powder composition, a polymer powder composition was prepared in the same manner as in Example 1, and three-dimensional modeling was performed to produce a three-dimensional object. The top powder temperature during modeling was consistent with the set value. The obtained three-dimensional object had no warping in the X direction, only a small warping in the Y direction, a white appearance, and good quality. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0112] [Example 7] A polymer powder composition was prepared in the same manner as in Example 6, except that the polymer particles were changed to (A-2), and three-dimensional modeling was performed to produce a three-dimensional object. The uppermost powder temperature during modeling was consistent with the set value. The obtained three-dimensional object had no warping in the X direction, only a small warping in the Y direction, a white appearance, and good quality. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0113] [Comparative Example 1] A polymer powder composition was prepared in the same manner as in Example 1, except that the composition was changed to 14 kg of polymer particles (A-1), 6 kg of glass fiber EPG70M-01N (manufactured by Nippon Electric Glass Co., Ltd.) as a reinforcing material, and the powder bed temperature during three-dimensional modeling was set to 204°C, and three-dimensional modeling was performed to produce a three-dimensional object. The uppermost powder temperature during modeling was consistent with the set value. The obtained three-dimensional object had no warping in the X direction and only a small warping in the Y direction, but had discolored yellowish brown. The polymer powder composition remaining in the tank 1 also discolored yellowish brown. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0114] [Comparative Example 2] A polymer powder composition was prepared in the same manner as in Example 1, except that glass beads GB731 (Potters-Barotini) were used as the reinforcing material, and three-dimensional modeling was performed to produce a three-dimensional object. The top powder temperature during modeling was consistent with the set value. The obtained three-dimensional object showed strong warping in both the X and Y directions, making it an unsuitable test piece for measuring mechanical properties. The powder composition used, the modeling method, and the obtained three-dimensional object are shown in Tables 1 and 2.

[0115] [Comparative Example 3] A polymer powder composition was prepared in the same manner as in Example 1, except that the composition was changed to 14 kg of polymer particles (A-1), 6 kg of glass fiber EPG40M-01N (manufactured by Nippon Electric Glass Co., Ltd.) as a reinforcing material, and 200 g of trimethylsilylated amorphous silica X-24-9500 (manufactured by Shin-Etsu Chemical Co., Ltd., D50 particle size 170 nm) was used, and three-dimensional modeling was performed to produce a three-dimensional model. The top powder temperature during modeling was consistent with the set value. The obtained three-dimensional model showed strong warping in both the X and Y directions, making it an unsuitable test piece for measuring mechanical properties. The powder composition used, the modeling method, and the obtained three-dimensional model are shown in Tables 1 and 2.

[0116] [Comparative Example 4] A polymer powder composition was prepared in the same manner as in Example 1, except that the composition was changed to 14 kg of polymer particles (A-3), 6 kg of glass fiber EPG70M-01N (manufactured by Nippon Electric Glass Co., Ltd.) as a reinforcing material, and 200 g of trimethylsilylated amorphous silica X-24-9500 (manufactured by Shin-Etsu Chemical Co., Ltd., D50 particle size 170 nm) was used, and three-dimensional modeling was performed to produce a three-dimensional model. The top powder temperature during modeling was consistent with the set value. The obtained three-dimensional model showed strong warping in the Y direction, making it an unsuitable test piece for measuring mechanical properties. The powder composition used, the modeling method, and the obtained three-dimensional model are shown in Tables 1 and 2.

[0117] [Table 1]

[0118] [Table 2] [Industrial Applicability]

[0119] The three-dimensional object of the present invention has excellent heat resistance and good quality without yellowing. The three-dimensional object obtained by the method for producing a three-dimensional object of the present invention can be used for functional prototypes and final products in mobility applications such as automobiles, aviation, and space, which require high heat resistance, medical applications such as prosthetic limbs, braces, hearing aids, and catheters, and electrical appliance applications such as home appliances and power tools. [Explanation of symbols]

[0120] 1. The tank where the model is formed 2. The tank stage where the model is formed 3. A supply tank in which the powder composition to be supplied is pre-filled 4. A tank stage pre-filled with the powder composition to be dispensed 5 Recoater 6. Thermal Energy 7 X, Y, Z coordinate system 8. Plane direction in which powder composition is laminated 9. Height direction of stacking powder composition 10 Three-dimensional objects 11 Pre-stacking height P material powder

Claims

1. A test piece having a width of 10 mm, a length of 80 mm and a thickness of 4 mm is prepared with the 80 mm length direction perpendicular to the movement of the recoater and the 4 mm thickness direction being the height direction in which the material powder is layered. The warp of the test piece in the 80 mm length direction is 1.5 mm / 10 cm or less. The three-dimensional object is obtained by a powder bed fusion method using a polymer powder composition, wherein the melting point of the polymer constituting the three-dimensional object is 200°C or higher and the yellowness of the three-dimensional object is 10 or less.

2. The three-dimensional structure according to claim 1 , wherein the polymer constituting the three-dimensional structure is a polyamide.

3. The three-dimensional object according to claim 2 , wherein the polyamide comprises at least one polyamide selected from the group consisting of polyamide 6, polyamide 610, polyamide 66, and copolymers containing any of these.

4. The three-dimensional structure according to claim 1 , wherein the three-dimensional structure contains a reinforcing material in an amount of 10% by mass or more and 80% by mass or less.

5. 2. The three-dimensional object according to claim 1, which is obtained by a powder bed fusion method using a polymer powder composition, wherein a test piece having a width of 10 mm, a length of 80 mm and a thickness of 4 mm is prepared such that the 80 mm length direction is parallel to the movement of a recoater and the 4 mm thickness direction is the height direction in which the material powder is layered, and the test piece has a heat distortion temperature of 160°C or higher when measured under a load of 0.45 MPa in accordance with JIS K7191-1 (2015).

6. The three-dimensional object according to claim 1 , comprising a surface having a surface roughness of less than 20 μm.

7. A method for manufacturing a three-dimensional object by a powder bed fusion method using a polymer powder composition, in which a test piece having a width of 10 mm, a length of 80 mm, and a thickness of 4 mm is prepared with the 80 mm length direction perpendicular to the movement of a recoater and the 4 mm thickness direction being the height direction in which the material powder is layered, and the warp of the test piece in the 80 mm length direction is 1.5 mm / 10 cm or less, wherein the melting point of the polymer constituting the polymer powder composition is 200°C or higher and the temperature of the uppermost powder layer of the powder bed is 200°C or lower.

8. The method for producing a three-dimensional object according to claim 7, wherein a lightness L(1) of the polymer powder composition before three-dimensional modeling and a lightness L(2) of the polymer powder composition remaining around the model after three-dimensional modeling are such that L(2) / L(1) is 0.85 or more and 1.05 or less.

9. The method for producing a three-dimensional object according to claim 7 , wherein the polymer powder composition contains a polyamide powder having a D50 particle size of 1 μm or more and 100 μm or less.

10. The method for producing a three-dimensional object according to claim 7 , wherein the polymer powder composition contains 10% by mass or more and 80% by mass or less of a reinforcing material having an average major axis of 3 μm or more and 120 μm or less and an average major axis / average minor axis ratio of 2 or more and 12 or less.

11. The method for producing a three-dimensional object according to claim 10, wherein the apparent density / tap density of the reinforcing material is 0.50 or more and 1.00 or less.

12. The method for manufacturing a three-dimensional object according to claim 7 , wherein a shrinkage rate on an XY plane of the three-dimensional object with respect to CAD data for the three-dimensional object is 2% or less.

13. The method for producing a three-dimensional object according to claim 7, wherein the temperature of the polymer powder composition supplied to the powder bed is 140°C or higher.

14. The method for producing a three-dimensional object according to claim 7 , wherein the preliminary stacking height is 15 mm or more.

Citation Information

Patent Citations

  • Resin powder for solid fabrication, device for manufacturing solid fabrication object, and method of manufacturing solid fabrication object

    JP2018196983A

  • Polymer powder, method for producing same and method for producing 3-dimensional model object

    WO2022181633A1